2021
DOI: 10.1038/s41598-020-79647-7
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric niche, nutrient partitioning and resource allocation in a solitary bee are sex-specific and phosphorous is allocated mainly to the cocoon

Abstract: Life histories of species may be shaped by nutritional limitations posed on populations. Yet, populations contain individuals that differ according to sex and life stage, each of which having different nutritional demands and experiencing specific limitations. We studied patterns of resource assimilation, allocation and excretion during the growth of the solitary bee Osmia bicornis (two sexes) under natural conditions. Adopting an ecological perspective, we assert that organisms ingest mutable organic molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…For the -KP diet (scarce in K and P), we observed signi cant improvement of cocoon development as well as a slight increase in male cocoon mass after supplementation with de cient nutrients, indicating that the elements scarce in this diet are important mainly for cocoon formation. The obtained results are in accordance with our previous study showing that the majority of P acquired during larval development is allocated to the cocoon and that a high proportion of K intake is used to build cocoons (Filipiak et al, 2021). The lack of improvement after supplementation that occurred in some cases might have been caused by additional (not studied) factors, e.g., the scarcity of colimiting nutrients (other than K, Na and P) (Bryś et al, 2021;Moerman et al, 2017;Vanderplanck et al, 2014;Vaudo et al, 2020;Zu et al, 2021) or the presence of poisonous substances (Eckhardt et al, 2013;Sedivy et al, 2011), various secondary metabolites (Palmer-Young et al, 2019) or the lack of an adequate microbial community (Dharampal et al, 2019(Dharampal et al, , 2020Steffan et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the -KP diet (scarce in K and P), we observed signi cant improvement of cocoon development as well as a slight increase in male cocoon mass after supplementation with de cient nutrients, indicating that the elements scarce in this diet are important mainly for cocoon formation. The obtained results are in accordance with our previous study showing that the majority of P acquired during larval development is allocated to the cocoon and that a high proportion of K intake is used to build cocoons (Filipiak et al, 2021). The lack of improvement after supplementation that occurred in some cases might have been caused by additional (not studied) factors, e.g., the scarcity of colimiting nutrients (other than K, Na and P) (Bryś et al, 2021;Moerman et al, 2017;Vanderplanck et al, 2014;Vaudo et al, 2020;Zu et al, 2021) or the presence of poisonous substances (Eckhardt et al, 2013;Sedivy et al, 2011), various secondary metabolites (Palmer-Young et al, 2019) or the lack of an adequate microbial community (Dharampal et al, 2019(Dharampal et al, , 2020Steffan et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies suggested that mismatches between the nutritional supply of pollen and the nutritional demands for building O. bicornis bodies and cocoons particularly concern sodium (Na), potassium (K), phosphorous (P), copper (Cu), and zinc (Zn) (Filipiak, 2019;Filipiak et al, 2021;Filipiak and Filipiak, 2020). Therefore, we used the concentrations and proportions of K, Na, P, Cu and Zn in the feeding experiment.…”
Section: Pollen Pool Selection and Treatments Used In The Feeding Experimentsmentioning
confidence: 99%
“…Fe, Zn, Mn)—might affect bee health. However, new insights are beginning to emerge, for both wild bees [98100] and honeybees [101]. Importantly, two aspects make an elemental approach particularly attractive.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In pollinator research, ecological stoichiometry has been used to study relationships between the chemical content and quality of bee food, and the consequences these may cause on the individual development of bees and the diversity of local pollinator communities ( Filipiak & Weiner, 2017 ; Filipiak et al, 2017 ). The maintenance of stoichiometric balance is important because inconsistency between the chemical composition of an organism’s tissues and that of its food sources strongly affects the organism’s life history traits, including fitness ( Filipiak, 2018 ; Filipiak, Woyciechowski & Czarnoleski, 2021 ). This suggests that the availability of suitable food and its elemental composition may influence the stoichiometric balance of individual pollinators ( Simanonok & Burkle, 2020 ).…”
Section: Introductionmentioning
confidence: 99%